2001
DOI: 10.1007/s007920100218
|View full text |Cite
|
Sign up to set email alerts
|

A catalase-peroxidase from a newly isolated thermoalkaliphilic Bacillus sp. with potential for the treatment of textile bleaching effluents

Abstract: A new thermoalkaliphilic bacterium was isolated from a textile wastewater drain and identified as a new Bacillus sp. (Bacillus SF). Because of its high pH stability and thermostability, a catalase-peroxidase (CP) from this strain has potential for the treatment of textile bleaching effluents. The CP from Bacillus SF was purified to more than 70.3-fold homogeneity using fractionated ammonium sulfate precipitation, hydrophobic interaction, and anion-exchange and gel-filtration chromatography. The native CP had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 32 publications
6
29
0
Order By: Relevance
“…In this study we have shown that the P. furiosus protein has rubredoxin-dependent peroxidase activity, which is comparable to that reported for archaeal and bacterial (nonrubrerythrin) peroxidases, such as from Archaeoglobus fulgidus (25), Thermus brockianus (45), Bacillus stearothermophilus (17), and Halobacterium halobium (5). The gene encoding rubrerythrin is adjacent to those encoding rubredoxin and superoxide reductase in the P. furiosus genome, consistent with a functional relationship between them (23).…”
Section: Discussionsupporting
confidence: 85%
“…In this study we have shown that the P. furiosus protein has rubredoxin-dependent peroxidase activity, which is comparable to that reported for archaeal and bacterial (nonrubrerythrin) peroxidases, such as from Archaeoglobus fulgidus (25), Thermus brockianus (45), Bacillus stearothermophilus (17), and Halobacterium halobium (5). The gene encoding rubrerythrin is adjacent to those encoding rubredoxin and superoxide reductase in the P. furiosus genome, consistent with a functional relationship between them (23).…”
Section: Discussionsupporting
confidence: 85%
“…strain SF decolorizes a number of azo dyes. This activity, however, cannot be attributed to the catalase-peroxidase previously isolated from this organism, which did not attack any of the tested dyes (13). An intracellular azoreductase (EC 1.7.1.6 [azobenzene reductase]) is responsible for the decolorization activity, as previously shown for other azo-dye-degrading microorganisms (11,31,36).…”
Section: Discussionsupporting
confidence: 53%
“…These observed half life times indicate a high potential for industrial processes like dye decolorization, detoxification, and transformation of phenolic and other compounds where high temperatures and pH values are common. Previously, an intracellular catalase-peroxide from this Bacillus SF has been described which also showed high stabilities at alkaline pH and high temperatures (Gudelj et al 2001). …”
Section: Ph Stabilitiesmentioning
confidence: 97%
“…Bacillus SF was isolated as described previously (Gudelj et al 2001). Cultures were grown on Caso-agar (Merck) plates pH adjusted with NaOH to 8.5 for 2 days at 55 • C and thereafter stored at 4 • C. The medium for liquid cultivation of Bacillus SF consisted of two different solutions which were combined after autoclaving.…”
Section: Cultivation Of Bacillus Sfmentioning
confidence: 99%